Exercise as a peripheral circadian clock resynchronizer in vascular and skeletal muscle aging - de Alencar Silva, Bruna Spolador [UNESP]; Uzeloto, Juliana Souza [UNESP]; Lira, Fábio Santos [UNESP]; Pereira, Telmo; Coelho-E-silva, Manuel J.; Caseiro, Armando (MDPI, 2021)
Aging is characterized by several progressive physiological changes, including changes in the circadian rhythm. Circadian rhythms influence behavior, physiology, and metabolic processes in order to maintain homeostasis; they also influence the function of endothelial cells, smooth muscle cells, and immune cells in the vessel wall. A clock misalignment could favor vascular damage and indirectly also affect skeletal muscle function. In this review, we focus on the dysregulation of circadian rhythm due to aging and its relationship with skeletal muscle changes and vascular health as possible risk factors for the development of sarcopenia, as well as the role of physical exercise as a potential modulator of these processes.
Keywords: Circadian rhythms; Clock genes; Inflammation; Sarcopenia; Skeletal muscle disfunction; Vascular disfunction